The spirit behind the mischievous misbehaviour of Kevin Khoo Keng Kok. - Lee, Qing Qing. (2010)
The Mischievous Misbehaviour of Kevin Khoo Keng Kok is an animated short film about a naughty, little tiger who learns to be good during Chinese New Year. It is a joint effort by 3 friends, Cai Lixian Clarisse, Seow Kim Siang and I. This report will be highlighting my involvement in the project, the various issues I faced as a producer and team player and how I managed them.